Der Quickborn im "3. Reich" : über das Verhältnis des Niederdeutschen zum Hochdeutschen und Niederländischen - Rohde, Wolfgang (1998)
For more than ninety years Quickborn has been - and still is - an influential periodical for people interested in Low German language, literature and/or movement. Quickborn also has been a participant and an object of cultural and political discourse during the "3rd Reich". Persons in the "Low German Movement" very often considered their language ("Niederdeutsch") as a bridge to other Germanic languages (and their speakers!), especially to Dutch, meaning Flemish (in Belgium) and Netherlandish. And undoubtedly, there have been some similar thoughts in Belgium and the Netherland. The first part of this publication (by Volker Georg) analyses the extent and quality of such (partial) parallels as reflected in Quickborn. The relationship between Low German and High German during the "3rd Reich" is a complicated one, too. ... The second part (by Dietmar Meyer) considers this relationship in analysing coneptual metaphors